HPLC-PDA-ESI-MS/MS Profiling and Anti-Biofilm Potential of Eucalyptussideroxylon Flowers - Mona M. Okba; Riham A. El-Shiekh; Mohammed Abu-Elghait; Mansour Sobeh; Rehab M. S. Ashour (MDPI AG, 2021)
The development of multidrug-resistant bacterial strains is a worldwide emerging problem that needs a global solution. Exploring new natural antibiofilm agents is one of the most important alternative therapies in combating bacterial infections. This study aimed at testing the antimicrobial potential of Eucalyptus sideroxylon flowers extract (ESFE) against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans prior to testing the antibiofilm activity against S. aureus, P. aeruginosa and C. albicans. ESFE demonstrated antimicrobial activity and promising inhibition activity against methicillin-resistant S. aureus (MRSA) biofilm formation up to 95.9% (p < 0.05) at a concentration of 0.05 mg/mL and eradicated C. albicans biofilm formation up to 71.2% (p < 0.05) at a concentration of 0.7 mg/mL. LC-MS analysis allowed the tentative identification of eighty-three secondary metabolites: 21 phloroglucinol, 18 terpenes, 16 flavonoids, 7 oleuropeic acid derivatives, 7 ellagic acid derivatives, 6 gallic acid derivatives, 3 phenolic acids, 3 fatty acids and 2 miscellaneous. In conclusion, E. sideroxylon is a rich source of effective constituents that promote its valorization as a promising candidate in the management of multidrug-resistant bacterial infections.